SISTEM KERJA VIRTUAL PHOTOSHOOT DITENGAH PANDEMI COVID-19 - Rangga Alfara; Dasrun Hidayat (Jurnal Ranah Komunikasi, 2021)
Virtual photoshoot is a photography trend nowadays. Where virtual photoshoots are an alternative business activity for photographers in the midst of a social distancing policy due to the Covid-19 pandemic outbreak. The method in this study used a qualitative descriptive method, and then a phenomenological study approach was carried out. The research sampling was carried out through purposive sampling method, namely the virtual photoshoot actors in the city of Bandung. The results in this study indicate the creative aspects of the virtual photoshoot which consist of methods, creative processes and obstacles. Meanwhile, the aspect of consumer trust consists of establishing a portfolio, educating the virtual photoshoot stage and targeting new potential markets. Whereas the virtual media photoshoots used consisted of social media references, media technology and the relationship between technology and photography media in order to improve business activities amid the ongoing Covid-19 pandemic.